Making Notes for Teaching Reading: The Implementation of Reading to Learn Program (R2L) in an EFL Classroom - Khusuma Dewi, Anggraeni; Kartika Ningsih, Harni (International Journal of Language Teaching and Education, 2026)
This paper investigates the implementation of note making from the Reading to Learn (R2L) program where students make notes from their reading texts and at the same time learn to read.  R2L is known to support literacy development but one specific phase, note making during the Joint Construction stage particularly in Indonesian EFL classrooms, remains largely unreported. This case study examines how the note making phase serves as a learning scaffold to teach reading. The study employs a pedagogic register to analyze classroom interactions and teacher-student relationships. The data were drawn from the classroom interaction recordings during the Joint Construction stage of R2L instruction. The findings indicate that pedagogical interaction during note making was characterized by explicit instruction, guided participation, affirmative scaffolding, and collaborative engagement between teacher and students. The assignment of reciter and scribe roles, along with prompting, checking, correction, and continuous affirmation, effectively encouraged active student participation in collaborative note construction. Note making activities helped students develop their awareness of vocabulary, spelling, pronunciation, and how texts are organized. This study provides both theoretical and practical insights by showing how systematic R2L note making can strengthen and improve literacy skills in EFL settings.